Website Bahan Ajar untuk Inovasi Digital untuk Meningkatkan Kualitas Pengajaran: - Frandes; Fitriani, Yessy; Ramanda, Febri (Jurnal Informatika Medis, 2025)
This article discusses the design and implementation of an instructional material website as a digital innovation aimed at enhancing the quality of teaching. The methods used include user needs analysis, interface design, and functionality testing. The results show that the instructional material website improves accessibility, flexibility, and student engagement in the learning process. This innovation also facilitates lecturers in systematically distributing teaching materials. The instructional material website has proven to be an effective solution in supporting a modern and efficient learning process.